The association of empowerment measures with maternal, child and family planning outcomes in Plateau State Nigeria by urban-rural residence - Kavita Singh; Ilene S. Speizer; Rashida-E Ijdi; Lisa M. Calhoun (BMC, 2021)
Abstract Background Nigeria is experiencing a high level of urbanization and urban poverty. Within Nigeria maternal and child health and family planning outcomes may differ by residence (capital city, urban/non-capital city and rural) as well as by measures of women's empowerment and wealth. This paper presents a detailed analysis of maternal and child health and family planning outcomes in Plateau State, Nigeria. Methods Data came from the 2017 Nigerian Urban Reproductive Health Initiative Sustainability Study. Multivariable logistic regression was used to study the associations between the key independent variables of residence, women's empowerment and wealth with having a skilled birth attendant at childbirth and childhood preventative visits. The women's empowerment variables included perceptions about household decision-making, financial decision-making, views on wife beating and having a prohibition, defined as a restriction on specific activities imposed by a woman's husband. Multinomial regression was used to study the association of the same factors with the family planning outcome which had three categories - no use, traditional method use and modern method use. Regressions were also run separately for urban and rural populations. Results Women in the capital city of Jos were significantly more likely to have a skilled birth attendant at childbirth, take a child to a preventative visit and use family planning than women in rural areas of Plateau State. Three of the four measures of empowerment (household decision-making, financial decision-making and having a prohibition) were significantly associated with the family planning outcome, while having a prohibition was negatively associated with having a skilled birth attendant at childbirth. In rural areas, women involved in financial decisions were significantly less likely to use a modern method compared to a traditional method. Wealth was a significant factor for all outcomes. Discussion State-level analyses can provide valuable information to inform programs and policies at a local level. Efforts to improve use of maternal and child health and family planning services in Plateau state, Nigeria, should consider women's empowerment, residence and poverty. Community education on the effectiveness of modern versus traditional methods and potential side effects of specific modern methods, may help women make informed decisions about contraception.